Increasing food diversity and nutritional yield: evaluating diverse cropping systems. A field study in Chapainawabganj District in Bangladesh - Saiful Islam; Cheesman, Stephanie; Maruf Hossen Shanto; Md. Arifur Rahaman; Hossain, M. Khaled; Jagadish Chandra Barman; Gathala, Mahesh Kumar; Krupnik, Timothy J. (TAFSSA, 2024)
Over the past two decades, Bangladesh has made significant strides in food production, particularly in rice, the country's primary crop (ADB, 2023). However, many people still lack access to a nutritious and diverse diet. Diets remain imbalanced, with rice contributing around 70% of total energy intake (BBS, 2010). The increased production of high-yielding cereals like rice, maize, and wheat has replaced more nutrient-rich cereals like millet, oats, and sorghum. New approaches are needed to produce nutrient-rich foods while using land efficiently. A farmers' participatory research trial was conducted in Chapainawabganj, and a research brief summarizes the results of the nutrition yield of diverse, intensified cropping systems compared to farmers’ common practices from 2022–23 in Chapainawabganj, Bangladesh.